Ready, steady … pause: integrating ICT into Shanghai preschools. Issue 2 (2nd April 2016) - Dong, Chuanmei; Newman, Linda
ABSTRACT: Western research over the last decade has shown that early childhood (EC) teachers' perspectives on the role of Information and Communication Technologies (ICT) in the early years strongly shape young children's experiences in educational settings and affect the integration of ICT into the classroom. The research in China is scant however. This article reports a study of Chinese EC teachers' views on the use of ICT in preschools. Data consist of illustrative original quotations generated from interviews with four teachers, as part of a larger study. This study shows that Chinese preschool teachers had an emerging understanding about social and technological impacts on the use of ICT in early childhood education (ECE), but they recognised the value of ICT for young children and themselves in a limited way. This restrained young children's active and meaningful use of ICT for early learning and development. We argue that there is a need to develop explicit ICT polices and curriculum guidelines for the ECE system that emphasise young children's active and creative use of ICT for early learning and development, and better support teacher learning.